FILM DOKUMENTER â€œHIROSHIMA: DROPPING BOMBâ€ INOVASI PEMBELAJARAN PENDIDIKAN KREATIF? - Mulyani, Santi Vera; Selvia, Belva; Lianti, Desi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstractâ€” Various information obtained by students is no longer fully obtained from the teacher but also from search engines like Google, Youtube applications and so on. This true picture is more easily obtained by students from elementary, junior high to senior high schools in this disruptive era encouraging teachers to utilize the technology as innovative learning in creative education. Real images of events in the past for example become critical questions in the era of openness as it is now encouraging writers to conduct research. Besides the lack of motivation to learn students on the subject of nationalism is also a driving force for writers. The purpose of this study was to determine the description of the use of the documentary film media